The effect of ultra_violet germidical to the removal of pathogens in rainwater harvester - Azyan, Rozlan (2018)
Water scarcity is a major problem in many developing countries. Malaysia has high precipitation thus this becomes the possible source for domestic use. In this study, ultra violet germicidal was used to disinfect rainwater in water samples collected from rainwater harvester tank in Gambang, Pahang. Then, it subjected to analysis for the presence of selected bacterial pathogens and potential pathogen of health concern for such Escherichia coli and Total Coliforms. This pathogen were found to be prevalent in rainwater samples with E. coli being the most prevalent potential pathogen in both types of samples. Samples were exposed to UV light for 5 minutes, 10 minutes, 15 minutes and 30 minutes. Water quality parameter for such pH, Colour, Turbidity, Total Dissolved Solid, Total Suspended Solid and Hardness was used. Tank water samples were also tested for fecal bacteria (Escherichia coli, total coliforms and other potential pathogens) using culture-based methods. The results then being compared with Ministry of Health drinking water standards. Among the sample that was exposed to UV light,all the parameters comply with the standards excepts for the value of Total Coliforms which exceed the maximum standard set. Based on this study, UV light is able to disinfect water with the help of other disinfection method.